Morphologic and Cytogenetic Description of the Small Red Brocket (Mazama bororo Duarte, 1996) in Brazil - Duarte, J. M B [UNESP]; Jorge, W. (De Gruyter, 2003)
We evaluated morphological and cytogenetic data for three animals similar to the species of deer previously described as the Small Red Brocket (Mazama bororo Duarte, 1996). We compared these animals with five M. americana, five M. nana and three hybrids between M. americana and M. nana. The M. bororo chromosomes can be standardized as follows : 8 group A chromosomes (large bi-armed) ; 2 group C chromosomes (small bi-armed) ; 4 group D chromosomes (large acrocentric) ; and 18 group E chromosomes (small acrocentric). There were great differences between this karyotype and those of M. nana and M. americana. With respect to external morphology, the animals in the present study had some similarities to M. americana and M. nana and great similarities with their hybrids. Most of the body measurements of M. bororo were significantly different from those of M. americana and M. nana, but similar to those of the hybrids. Mazama bororo is distributed in the last remnants of the Atlantic forest, extending from the southeastern part of the State of São Paulo to the northeastern part of the State of Paraná, Brazil. The rapid destruction of the Atlantic Forest requires urgent conservation measures for the species.
Keywords: Brazil; Cervidae; Cytogenetic; Mazama bororo; Morphology; Small red brocket; cytogenetics; deer; morphology; taxonomy; South America; Animalia; Mammalia; Mazama; Mazama americana; Mazama nana